Individual selection in a genetic test with 43 advanced progenies of camu-camu Myrciaria dubia Kunth (McVaugh) in floodable plot near Iquitos, Peruvian Amazon (Scientia Agropecuaria, 2020)
The research summarized and validated the individual selection of camu-camu (Myrciaria dubia (Kunth) McVaugh) plants. 43 progenies, previously selected in genetic tests and fields of producers of flood areas, were evaluated. Each progeny was installed in a row of 10 half-sister plants, with a space of 3x2 m. Using the SELEGEN (Reml / Blup) Model 63 program, four crops were analyzed, and individuals were selected for each of the 16 descriptors evaluated. For fruit yield, the Tipishca-Río Tigre population stood out, occupying 5 of the first 10 places. The individuals TT0725-4 (Tigre-Tipishca) turned out to be a natural recombinant for fruit yield / weight. And individual 64-8 turned out to be triple recombinant (yield / fruit weight / ascorbic acid). The descriptors with the highest genetic control with r ≥ 0.30 were: average fruit weight, brix degrees, plant height, number of basal branches and petiole length. The criteria of similarity of the morphological markers with the fruit yield are proposed as predictive indexes of productivity. The plant height at two years of age was the most important.
Keywords: amazon rainforest; fruit food; genetic evaluation; genetic selection; tree breeding.